Genetic variation that predicts platinum sensitivity reveals the role of miR-193b* in chemotherapeutic susceptibility - Ziliak, Dana (2012)
Platinum agents are the backbone of cancer chemotherapy. Recently we identified and replicated the role of a single nucleotide polymorphism (SNP, rs1649942) in predicting platinum sensitivity both in vitro and in vivo. Using the CEU samples from the International HapMap Project, we found the same SNP to be a master regulator of multiple gene expression phenotypes, prompting us to investigate whether rs1649942-mediated regulation of microRNAs (miRNAs) may in part contribute to variation in platinum sensitivity. To these ends, sixty unrelated HapMap CEU I/II samples were utilized for our discovery-phase study using high-throughput genome-wide miRNA and gene expression profiling. Examining the relationships among rs1649942, its gene expression targets, genome-wide miRNA expression and cellular sensitivity to carboplatin and cisplatin, we identified 2 platinum-associated miRNAs (miR-193b* and miR-320) that inhibit the expression of five platinum-associated genes (CRIM1, IFIT2, OAS1, KCNMA1 and GRAMD1B). We further replicated the relationship between the expression of miR-193b*, CRIM1, IFIT2, KCNMA1 and GRAMD1B, and platinum sensitivity in a separate HapMap CEU III dataset. We then showed that over-expression of miR-193b* in a randomly selected HapMap cell line results in resistance to both carboplatin and cisplatin. This relationship was also found in 7 ovarian cancer cell lines from NCI60 dataset and confirmed in an ovarian cancer cell line (OVCAR-3) that over-expression of miR-193b* leads to increased resistance to carboplatin. Our findings highlight a potential mechanism of action for a previously observed genotype-survival outcome association. Further examination of miR-193b* in platinum sensitivity in ovarian cancer is warranted.